2011
DOI: 10.1186/1471-2458-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adults' intention to vaccinate against pandemic swine flu

Abstract: BackgroundVaccination is one of the cornerstones of controlling an influenza pandemic. To optimise vaccination rates in the general population, ways of identifying determinants that influence decisions to have or not to have a vaccination need to be understood. Therefore, this study aimed to predict intention to have a swine influenza vaccination in an adult population in the UK. An extension of the Theory of Planned Behaviour provided the theoretical framework for the study.MethodsThree hundred and sixty two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(199 citation statements)
references
References 27 publications
9
175
4
1
Order By: Relevance
“…Subsequently, these consumers’ dietary patterns have changed swiftly toward higher levels of consumption of meat products, while those in the low‐income category continue to suffer extreme poverty and malnutrition (Kandala, Madungu, Emina, Nzita, & Cappuccio, 2011; Rossi, Hoerz, Thouvenot, Pastore, & Michael, 2006). Generally, beef, goat, pork, chicken, and rabbit are the meats most consumed in Eastern DRC.…”
Section: The Meat Market In the Democratic Republic Of Congomentioning
confidence: 99%
“…Subsequently, these consumers’ dietary patterns have changed swiftly toward higher levels of consumption of meat products, while those in the low‐income category continue to suffer extreme poverty and malnutrition (Kandala, Madungu, Emina, Nzita, & Cappuccio, 2011; Rossi, Hoerz, Thouvenot, Pastore, & Michael, 2006). Generally, beef, goat, pork, chicken, and rabbit are the meats most consumed in Eastern DRC.…”
Section: The Meat Market In the Democratic Republic Of Congomentioning
confidence: 99%
“…More generally, the belief that people's importance to self and support vaccination is positively associated with vaccination intention and behavior (e.g., Allen et al 2010 ;Flood et al 2010 ;Myers and Goodwin 2011 ). For example, young women who felt their mothers might not want them to be vaccinated were much less likely to complete the three-dose HPV vaccine series than those who felt their mothers would "defi nitely" want them to be vaccinated .…”
Section: Normsmentioning
confidence: 95%
“…The majority of studies were disease specific. Two studies examined intentions to be vaccinated (protective action or preparedness behavior) for H1NI, finding that emotions, perceptions about the disease (severity and susceptibility) and of the vaccine (cost and effectiveness), and prior experience were predictors (Myers & Goodwin, 2011;Setbon & Raude, 2010). [insert Table 3 here] A third H1N1 study found that affective response fully mediated the relationship between cognitive and social--contextual factors and compliance with recommended behaviors (Prati, Pietrantoni, & Zani, 2011).…”
Section: Epidemicsmentioning
confidence: 99%